Prenatal Environment That Affects Neuronal Migration - Hwang, Hye M.; Ku, Ray Y.; Hashimoto-Torii, Kazue (Frontiers in Cell and Developmental Biology, 2019)
Migration of neurons starts in the prenatal period and continues into infancy. This developmental process is crucial for forming a proper neuronal network, and the disturbance of this process results in dysfunction of the brain such as epilepsy. Prenatal exposure to environmental stress, including alcohol, drugs, and inflammation, disrupts neuronal migration and causes neuronal migration disorders (NMDs). In this review, we summarize recent findings on this topic and specifically focusing on two different modes of migration, radial, and tangential migration during cortical development. The shared mechanisms underlying the NMDs are discussed by comparing the molecular changes in impaired neuronal migration under exposure to different types of prenatal environmental stress.